MODULE AND AUDIOVISUAL PACKAGE INTERVENTIONS IN INCREASING STUDENTS' KNOWLEDGE AND HARD SKILL IN MATERNITY NURSING COURSES - Mutmainnah, Muthia; Meinarisa, Meinarisa; Mulyani, Sri (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
COVID-19 has changed the order of education in Indonesia. There is a big change in learning from formal education in the classroom to learning from home, with an online system. The online education system is certainly not easy. In addition to the personal discipline to study independently, there are facilities and resources that must be provided. Laboratory activities that hone students' abilities in developing skills for patients were forced to turn into audiovisual learning. In maternity nursing learning there are practices carried out in laboratories that develop students' hard skills and knowledge The design of this research is pretest and posttest without control group. The implementation of the audiovisual learning and module intervention was given in 4 sessions consisting of pregnancy, childbirth, newborns and the postpartum period. The questionnaire used in this study was a knowledge questionnaire and hard skill assessment on students using zoom. Number of respondents are 63 respondents. The results of the study show that there is an effect of audiovisual learning on students’ knowledge p=0,001 and soft skill p=0,001. This study shows an increase in the score of 80% of the number of respondents. This research recommends giving audiovisual learning to improve knowledge laboratory skills in maternity nursing.